WANITA HAMIL SEBAGAI PERLINDUNGAN NASAB ANAK DALAM KOMPILASI HUKUM ISLAM - Hermanto, Agus (Istinbath : Jurnal Hukum, 2016)
Marriage is a bond between the inner and outer wanitasebagai a man with a husband and wife with the aim of forming a family (household) were happy and everlasting based on God. The scholars agreed that the wedding for pregnant women should be carried out again after giving birth. Reconstruction of the law relating to the validity of the marriage ceremony for a pregnant woman, in this case the Indonesian Islamic scholars consider the elements of sociological and psychological especially the local culture of Indonesian society, which is a compromise approach to customary law. Pengkompromian fact that in terms of the deviation in the teaching of fiqh associated with sociological and psychological factors. The main objective principle of the permissibility of marrying pregnant is to provide a definite legal protection to children in the womb, even though the status bastard child, although the Islamic Law Compilation impressed shows the government's attitude is very ambivalent / ambiguous. Perkawinan ialah ikatan lahir batin antara seorang pria dengan seorang wanitasebagai suami isteri dengan tujuan membentuk keluarga (rumah tangga) yang bahagia dan kekal berdasarkan Ketuhanan Yang Maha Esa. Para ulama sepakat bahwa pernikahan bagi wanita hamil haruslah dilaksanakan kembali setelah melahirkan. Rekonstruksi hukum terkait dengan keabsahan akad nikah bagi wanita hamil, dalam hal ini ulama Islam Indonesia mempertimbangkan unsur-unsur sosiologis dan psikologis khususnya budaya lokal masyarakat Indonesia, yang merupakan pendekatan kompromistis dengan hukum adat. Pengkompromian itu ditinjau dari segi kenyataan terjadinya ikhtilaf dalam ajaran fikih dihubungkan dengan faktor sosiologis dan psikologis. Tujuan utama azas kebolehan kawin hamil adalah untuk memberikan perlindungan hukum yang pasti kepada anak yang dalam kandungan, walaupun anak tersebut statusnya anak zina, walaupun Kompilasi Hukum Islam tersebut terkesan memperlihatkan sikap pemerintah yang sangat ambivalen/ambigu.